Heartbleed Bug: AnOpenSSL Heartbeat Vulnerability - Gujrathi, Siddharth (International Journal of Computer Sciences and Engineering, 2014)
Due to exponential growth of Internet, Internet user privacy and data integrity is main concern for developers and service providers over Internet. Keeping this aim in mind Internet has adopted web encryption technique called OpenSSL, which gives a way to secure data and user privacy over Internet. Most of security sensitive application on Internet such as Internet banking, eCommerce, eGoverment has adopted this new technique which gives them a trustworthy way to connect them with their users. OpenSSL is only security mechanism having such reliability of work and has used from long time. But researchers have disclosed a serious vulnerability in this standard Web encryption software known as ï¿½Heartbleedï¿½, the bug can give hackers access to personal data like credit card numbers, usernames, passwords, and, perhaps most importantly, cryptographic keysï¿½which can allow hackers to impersonate or monitor a server. This research paper provides a detail working of Heartbleed bug and how this bug can affect your online privacy and data integrity.